SMART HOME SYSTEM SECURITY RISK ASSESSMENT (Computer systems and information technologies, 2022)
The concept of the Internet of Things became the basis of the fourth industrial revolution, which allowed to transfer the processes of automation to a new saber. As a result, automation systems, such as smart homes, healthcare systems and car control systems, have become widespread. The developers of such systems primarily focus their efforts on the functional component, leaving safety issues in the background. However, when designing and operating IoT systems, it is equally important to assess potential bottlenecks and develop complete and comprehensive strategies to mitigate and eliminate the negative effects of cyberattacks.The purpose of this study is to identify possible cyber threats and assess their impact on critical information objects in the smart home system. To achieve this goal, the three-level architecture of the smart home system is considered and a review of known cyber threats for each level is conducted. The critical information objects in the smart home system are the containers in which the information objects are stored, the risk assessment criteria and the cyber threat scenarios. The information security risks of the smart home system were assessed using the OCTAVE Allegro methodology for the information object that presents the information collected by the smart home sensors.
Keywords: security risk assessment, smart home, critical information object, threats